On the use of images in research with children: photo elicitation and other methodologies in the Brazilian investigative panorama (Práxis Educativa, 2021)
For a long time, photography, in its dynamic and even paradoxical aspects, has been composing the panorama of research in the field of education, both theoretically and methodologically. Therefore, in this article, we aim to discuss photography as a decisive element of a particular methodology, photo-elicitation. More specifically, we are interested in dealing with photo-elicitation, as it is dynamized in the dialogue with a particular group of subjects, the children. To this end, initially, we present a bibliographic survey on research with/about children who, methodologically, used images to establish unique dialogues with them (the children) – especially those pieces of research that make open use of the photo-elicitation method. Then, based on the analysis of the results of this mapping and, together with it, our research experiences with children, we systematized a set of advantages and challenges that are imposed on this specific way of composing the research field and its strategic data production.Keywords: Qualitative methods. Child. Photo-elicitation.